ExBWS: extended bioinformatics web services for sequence analyses. (22nd September 2021) - Penchovsky, Robert; Pavlova, Nikolet; Kaloudas, Dimitrios
The extended bioinformatics web services (ExBWS) represent a significant extension of the published EBWS PHP-based server providing useful tools for analyses of DNA, RNA, and protein sequences. Six new web-based applets are freely available via the ExBWS to the user. They include a DNA/RNA translator, an AminoCODE transformer, a virtual PCR analyser, a protein hydropathy plotter, protein reverse translator, and a Eukaryotic ORF finder. Each applet includes some novel feature. The AminoCODE transformer takes a protein sequence from one letter code to three and vice versa, the virtual PCR analyser generates fragments with or without overhangs, the protein hydropathy plotter makes hydropathy plots of 10 frames of the input sequence, the reverse translator converts proteins to DNA according to the highest codons bias present in the selected organism. The Eukaryotic ORF finder searches for introns in the query sequence and translates ORFs of the processed sequence into proteins. All programs are freely available at http://penchovsky.atwebpages.com/applications.php.